2002
DOI: 10.1007/bf02254980
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for mitochondrial disease by delivering restriction endonucleaseSmaI into mitochondria

Abstract: The restriction endonuclease Sinai has been used for the diagnosis of neurogenic muscle weakness, ataxia and retinitis pigmentosa disease or Leigh's disease, caused by the Mt8993T~G mutation which results in a Leu156Arg replacement that blocks proton translocation activity of subunit a of FoF1-ATPase. Our ultimate goal is to apply Sinai to gene therapy for this disease, because the mutant mitochondrial DNA (mtDNA) coexists with KARG E P~Fax+41 61 306 12 34 E-Mail karger@karger.ch w-~.~.karger, corn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…The number of nucleoids decreased with ApaLI induction but recovered along with the mtDNA levels. These observations are similar to those reported by Tanaka et al (9), who showed a reduction in mtDNA copy number upon expression of SmaI or EcoRI in mitochondria of cultured cells (9). Taken together, our results indicate that the shift in mtDNA heteroplasmy by mitochondrially targeted restriction endonucleases is rapid and specific.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The number of nucleoids decreased with ApaLI induction but recovered along with the mtDNA levels. These observations are similar to those reported by Tanaka et al (9), who showed a reduction in mtDNA copy number upon expression of SmaI or EcoRI in mitochondria of cultured cells (9). Taken together, our results indicate that the shift in mtDNA heteroplasmy by mitochondrially targeted restriction endonucleases is rapid and specific.…”
Section: Discussionsupporting
confidence: 93%
“…Tanaka et al (9) showed that cultured cells with the T8399G mutation underwent a shift in heteroplasmy when a mitochondrially targeted SmaI was expressed. However, it took five cycles of transfection to completely eliminate the mutated mtDNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a basic study of mitochondrial delivery using MTS, pDNA encoding an MTS-fused protein was used to transfect cultured cells. The MTS directs the cargo protein inside the mitochondria, where it is then cleaved, allowing for localization and function of the fused protein [146][147][148] (Fig. 6).…”
Section: Mitochondrial Protein Delivery Using the Mitochondrial Tamentioning
confidence: 99%
“…On the other hand, oligo DNA (linear DNA), as a therapeutic agent for muted mtDNA, was investigated, in order to repair mutated mtDNA and inhibit the replication of mutated mtDNA [34,35]. Moreover, the use of a restriction enzyme (protein) would be expected to be useful and productive for the selective digestion of mutated mtDNA [36]. We conclude that the flexibility associated with the design of such a MEND will meet the requirements for drug delivery systems for mitochondrial gene therapy and diagnosis.…”
Section: Discussionmentioning
confidence: 99%